Plastic and Reconstructive Surgery of Burns An Atlas of New Techniques and Strategies - Grishkevich, Viktor M. (Springer International Publishing, 2018)
This comprehensive atlas provides a step-by-step guide of new techniques in burn surgery and enables readers to identify the appropriate treatment plan and best possible procedure for each patient pre-surgery before delving into a variety of different surgical possibilities for treatment and recovery. Plastic and Reconstructive Surgery of Burns - An Atlas of New Techniques and Strategies presents new solutions in plastic and reconstructive surgery for burns built upon tried and true techniques of contracture restoration using various flaps and skin grafts. Accompanying illustrations and schemes allow the reader to visualize the process from mapping, dissecting and closing the wound. Preoperative and postoperative results are compared, with extensive illustrations and pictures that cover areas of the body most commonly treated for burns including face, neck, breast, torso, arms, legs, hands, and feet. Outcomes of the surgeries including full functional and aesthetic restoration of treated patients are meticulously photographed and provided alongside each technique. New classifications are presented based on contracture anatomy which showcase the development of new flaps and techniques that elevate functional and aesthetic rehabilitation of burned patients to a new level. The culmination of the decades long career of renowned plastic surgeon, Viktor M. Grishkevich, many new and original techniques, currently unpublished in U.S. literature, are detailed in depth alongside techniques uniquely designed by Dr. Grishkevich and previously published around the world. Plastic and Reconstructive Surgery of Burns - An Atlas of New Techniques and Strategies, has international reach and is meant for plastic and reconstructive surgeons with specialties in hand, maxillo-facial, facial, and ENT. Due to its detailed nature, the atlas is also appropriate for residents in the related fields of surgery as well.